Bases conceituais para uma política linguística do português/italiano nas escolas : Caxias do Sul RS - Pinheiro, Luciana Santos (My University, 2014)
Linguistic contacts between the national official language, Portuguese, and the ones from migration settlements are due to linguistic and cultural diversity presents in Brazil, leading to a linguistic and cultural exchange in a bilingual context. In the case of Caxias do Sul city, inserted in the Italian Colonization Region of Rio Grande do Sul (ICR), the context here found is of a passive and restrict bilingualism of Portuguese/Italian dialect. Many different authors reinforce the importance of ensuring to the group of immigrant descendants their linguistic rights that historically has been suffering with the alternation of linguistic policies from the government, which sometimes accepts it, other times repudiates their original language, and also addressing to a lack of research in this area. The aim of the present study is to put together the conceptual basis to be used by an adequate linguistic policy towards the Italo-descendants group of Caxias do Sul - RS/Brazil - bilingual situation. As an example of what is already been done in other cities, we defend the introduction of the teaching and the use of the standard Italian language as a way to characterize a territory, and not only as a mark of an ethnic group, avoiding any kind of linguistic prejudice. Semi-structured interviews were conducted in search of gaining substantial information to the analysis of the introduction process of the chosen foreign language in Caxias do Sul city (public and private) schools, as well as considering the University role in this process, and finally, highlighting the importance of Italian as a working language. In possession of the collected data and it analysis, the importance of teaching/learning the Italian standard language is raised as an indispensable part to the community both in the cultural and economic sphere to the ICR.
Em virtude da diversidade linguística e cultural presentes no Brasil, provenientes de processos migratórios (europeu, asiático, etc.) de colonização, ocorrem os contatos dessas línguas com a língua oficial nacional, o português, dando origem a um intercâmbio linguístico e cultural num contexto de bilinguismo. No caso do município de Caxias do Sul, inserido na Região de Colonização Italiana-RS, o contexto é de bilinguismo do português/dialeto italiano passivo e restrito. Diversos autores afirmam a necessidade de assegurar os direitos linguísticos aos grupos descendentes de imigrantes que, historicamente, vêm sofrendo alternância nas políticas linguísticas por parte do governo que ora aceita, ora repudia sua língua de origem, e de suprir uma carência de pesquisas nessa área. Este estudo apresenta bases teóricas para uma política lingüística adequada à situação de bilingüismo do grupo ítalo-descendente de Caxias do Sul, RS/Brasil. A exemplo do que já vem sendo feito em outros municípios, defende-se o ensino e uso da língua italiana como forma de caracterização de um território, e não apenas como marca de um grupo étnico, evitando assim, o preconceito lingüístico. O instrumento adotado foi o das entrevistas semi-estruturadas visando obter informações para a análise do processo de escolha das línguas estrangeiras introduzidas nas Escolas do município de Caxias do Sul, bem como considerar o papel da universidade nesse processo e destacar a importância do italiano como língua de trabalho.
Keywords: Bilinguismo; LINGUISTICA; Política linguística; Cultura; Direitos linguísticos; Região; Língua italiana; Dialeto italiano; Bilingualism; Culture; Linguistic rights; Linguistic policy; Region